Exposure to Armed Conflict and Monitoring as Predictors of Aggression in a Population Immersed in a Long-Term Conflict - Garcia-Serrano, A (John Wiley and Sons Inc, 2024)
As armed conflict can influence social behavior, exposed individuals would experience modulated executive functioning, crucial to regulating aggressive responses. Since it is still unclear whether there is an association, this study examines the relationship between performance in executive functions and expression of reactive and proactive aggression, measured using the Reacting Proactive Aggression Questionnaire. The sample includes 128 civilians and ex-combatants with different levels of exposure to the Colombian armed conflict. The study found that reactive aggression was directly linked to conflict exposure and was also influenced by age and monitoring ability. This suggests that an updated working memory and age play a role in reactive aggression. In contrast, proactive aggression was directly linked to conflict exposure but not to specific executive functions. In conclusion, individuals with less monitoring who live in high-conflict regions present an increased likelihood of reactive aggression. Additionally, reasonable executive control of thoughts and actions, which involves updating past experiences, appears to be crucial in social contexts, especially violent ones. These findings shall inform interventions and public policies that address the psychosocial risks of aggressive behaviors. © 2024 International Society of Political Psychology.